(untitled) (Al-Academy, 2016)
Each art has its own language. Per his style as an artist, which is characterized by the other. The methods differ and vary expressive art to another depending on the tools and methods used, and is a theatrical phenomenon did, and see, and touch, grasp, understand, and imagine, and emotion, and the blending of ideas and images. When unable to speak the language of the traditional theater For the delivery of a specific meaning or a single non-current at the time the highlight of our new language with a very wide area up to the extent of the unification of the languages of the world as it is in fine painting, it’s the body of actor language, so it has become a mime art, which expressed Representative meanings reference and movement of various physical and expressions . Representative in the exercise of this difficult type of performance should be able to express an idea and passion so that entices the audience a sense that they lack the provision of traditional word in traditional theater, but in order to know the performance of the actor in the silent theater emerged several questions resulted in the emergence of the research problem, namely, Actor performance features in the types of theatrical silent. In order to methodological research it was founded researcher theoretical framework to research problem, objectives and limits. Then the theoretical framework that Two topics: The first topic (mime: the beginnings and ends) in which he addressed the researcher beginnings of mime and the reasons for his appearance and Agheiat cation of its founding. And second (kind of silent theater) where the researcher explained the difference between the types of mime exclusive and differentiated from representation which does not include theatrical dialogue (the job playwright). Then research procedures, which the researcher identified a sample of his research included performing Representative of three offers. Then came the researcher several results. Then put the researcher list of sources of research and review. Finally, the title and abstract in English.